2018
DOI: 10.1111/nhs.12430
|View full text |Cite
|
Sign up to set email alerts
|

Adverse events witnessed by nursing students during clinical learning experiences: Findings from a longitudinal study

Abstract: No evidence from any longitudinal study design has been reported to date with regard to patient safety (PS) incidents witnessed by nursing students during their training. Therefore, with the aim of closing this gap in available knowledge, a longitudinal study was performed from 2012 to 2015 by involving all nursing students (n = 145) enrolled in two Italian nursing programs. At the end of each academic year, students were invited to report in writing all PS incidents witnessed during their clinical learning ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…A cross-sectional survey showed that approximately 40%-50% of medical errors are related to nursing interns [5]. In addition, nearly 17%-53.2% of nursing interns reported nursing safety events [6]. Unsafe care can increase morbidity and mortality, additional medical expenses, disability, nosocomial infections, and low healthcare efficiency [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional survey showed that approximately 40%-50% of medical errors are related to nursing interns [5]. In addition, nearly 17%-53.2% of nursing interns reported nursing safety events [6]. Unsafe care can increase morbidity and mortality, additional medical expenses, disability, nosocomial infections, and low healthcare efficiency [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, when starting their clinical practice, nursing interns are unfamiliar with hospital environments, unskilled in operation, and lack theoretical knowledge and communication skills; these limitations could pose occupational safety hazards (Gorgich et al, 2016 ; Song & Guo, 2019 ; Stevanin et al, 2015 ). Previous studies have shown that approximately 17%–53.2% of nursing interns reported adverse nursing safety events (Stevanin et al, 2018 ), although most are not reported (Stevanin et al, 2018 ). Contrastingly, few nursing interns accept training for preventing and coping with workplace violence.…”
Section: Introductionmentioning
confidence: 99%
“…33 In the current study, 26 (5.8%) participants exhibited dishonest behaviour related to the application of therapy and 13 (2.9%) failed to report a patient fall, which is comparable to other similar studies. 13,[34][35][36][37] Stevanin 35 reported that nursing students witnessed or reported a mean of 3.8 patient safety incidents in 1000 days of clinical practice in the hospital, and most of these incidents were related to the application of therapy. In addition, according to Reid-Searl et al, 34 approximately one-third of students were involved in activities which resulted in a therapeutic error.…”
Section: Incidence Of Dishonest Behaviour In the Clinical Settingmentioning
confidence: 99%
“…Types of incidents reported. Stevanin et al [30] described PSI incidence rates that were witnessed or reported by first, second and third year nursing students. Overall, students witnessed or reported 3.8 PSIs per 1000 days of training in a clinical setting and most PSIs were related to medication administration.…”
Section: Themesmentioning
confidence: 99%
“…Overall, students witnessed or reported 3.8 PSIs per 1000 days of training in a clinical setting and most PSIs were related to medication administration. [30] Similarly, Santos [31] found that students most often committed medication errors, but the largest proportion of PSIs were related to care implementation, which encompasses skills such as adhering to guidelines and knowledge application. In examining only medication errors, Walsh et al [32] reported the three most common error types, which were: (1) not administering a medication within the appropriate time frame, (2) administering the medication at the wrong time, and (3) inaccurately documenting medication administration.…”
Section: Themesmentioning
confidence: 99%